Instrumentos de evaluación y su incidencia en el aprendizaje de los estudiantes de la Escuela de Educación Básica “General Julio Alberto Amores Tovar” del Cantón La Maná. Periodo 2014-2015 plan de capacitación - Allauca Guamán, Lorena Ximena (2016)
The research theme of assessment instruments and their impact on student learning basic school education "General Julio Alberto Amours Tovar" La Maná Canton. 2015-2016 period aims to assess the impact of assessment tools in student learning theoretical foundation also aims evaluation processes and learning, identify the assessment tools used by teachers in the school under study for it it is proposed as an alternative solution to the problem of designing a training plan for the implementation of evaluation instruments. that improves processes to improve learning. Research development for a non-experimental design was used since no variables are modified the exploratory and descriptive research is intended to contribute to the needs of improving educational practice facility enriching the knowledge of teachers and improving student learning The research provides information about the importance of the evaluation process in basic education as part of the development of new skills and a safe and effective learning through the application of several assessment instruments, measuring student attitudes and skills in response to the process educational; ie shows the knowledge, skills and values developed as a result of the educational process and its application in everyday life.